Optimization of process parameter variations for 16nm DG-FinFET using Response Surface Methodology-Central Composite Design - Roslan A.F.; Salehuddin F.; Zain A.S.M.; Kaharudin K.E.; Ahmad I.; Hazura H.; Hanim A.R.; Idris S.K.; Hamid A.M.A. (Institute of Physics Publishing, 2023)
Design; FinFET; Leakage currents; Polysilicon; Surface properties; Threshold voltage; Central composite designs; International Technology Roadmap for Semiconductors; Optimization of process parameters; Optimization techniques; Process parameters; Response surface method; Response surface methodology; Sub-threshold swing(ss); Semiconductor doping